1994
DOI: 10.1002/art.1780371005
|View full text |Cite
|
Sign up to set email alerts
|

Increased frequency of vβ17‐positive t cells in patients with rheumatoid arthritis

Abstract: Objective. To identify the T lymphocytes that mediate disease in rheumatoid arthritis (RA). Methods. A panel of monoclonal antibodies reactive with T cell receptor (TCR) Vp gene products was used to analyze the RA T cell repertoire.Results. Of 5 TCR Vp gene products studied, only Vpl7-positive T cells were increased in peripheral blood and synovial fluid (SF) from RA patients, compared with controls (P < 0.01 and P = 0.0006, respectively).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

1996
1996
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(22 citation statements)
references
References 55 publications
2
20
0
Order By: Relevance
“…Moreover, in this study, we did not detect skewed BV17 and other BV genes that were described in Caucasian RA patients. [19][20][21][22][23] The observations have raised the possibility that in this study, overexpression of BV16 and lack of skewed BV17 and some other BV genes described in other reports may be characteristically associated with Chinese RA patients, while BV14 skewing is common to both Caucasian and Chinese patients with RA. Such discrepancies in BV gene skewing may be attributable to both genetic background (eg HLA genes) and environmental factors of geographic significance.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…Moreover, in this study, we did not detect skewed BV17 and other BV genes that were described in Caucasian RA patients. [19][20][21][22][23] The observations have raised the possibility that in this study, overexpression of BV16 and lack of skewed BV17 and some other BV genes described in other reports may be characteristically associated with Chinese RA patients, while BV14 skewing is common to both Caucasian and Chinese patients with RA. Such discrepancies in BV gene skewing may be attributable to both genetic background (eg HLA genes) and environmental factors of geographic significance.…”
Section: Discussionsupporting
confidence: 50%
“…[19][20][21][22][23] Analysis of CDR3 of overexpressed BV genes has revealed some clonotypes that only exist in rheumatoid synovium but not peripheral T cells, suggesting T-cell clonal expansion in the affected joints in RA. [24][25][26] However, clonality and TCR BV gene usage of infiltrating T cells in RA SF or membranes are relatively heterogeneous, which complicates BV gene analysis using regular or semiquantitative PCR.…”
Section: Introductionmentioning
confidence: 99%
“…TCRBJ gene expression, in association with TCRBV5, 13, and 17 family genes, was examined in PBL from six pairs of healthy monozygotic twins, six pairs of monozygotic twins discordant for RA, and five normal individuals (total of 29). The BV5, 13, and 17 gene families were selected, because of previous reports indicating that the frequencies of T cells with BV5, 13, and 17 gene products were more abundant in synovial fluid and/or PBL from RA patients (12,13). The TCRBJ gene frequencies of all 29 donors are depicted in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Four other studies have shown a higher frequency of particular TCR chain usage in CD8+ T cells from RA patients, namely TCR V,3 (33,35), TCR V,17 (36), and TCR V,12S1 expansions (37); 3 of the 4 studies did not investigate the CD8high+(CD57+) subset. Oligoclonality in both CD8+, CD57-and CD8high+(CD57+) populations of TCR V,3+ T cells was found in RA patients but not in controls (50% versus 4%) by a multiplex PCR assay (35).…”
Section: Discussionmentioning
confidence: 99%